From Heart to Heart: Teacher Strategies in Teaching English to Students with Special Needs through Narrative Inquiry - Mirnawati; Dzulfikri (Al-Qalam Institute, 2025)
Teaching English to students with Down Syndrome presents a distinctive pedagogical challenge that extends well beyond the application of conventional instructional methods. While inclusive education has gained increasing momentum globally, the specific experiences of teachers working with students with Down Syndrome in English as a Foreign Language (EFL) contexts remain underexplored, particularly within the Indonesian Sekolah Luar Biasa (SLB) setting. This study aims to explore the lived experience of an English teacher navigating the challenges and strategies involved in teaching English to a student with Down Syndrome, with particular attention to how her pedagogical approach evolved over time. Employing a qualitative approach through a narrative inquiry design, this study analyzed the teacher's journey across three analytical dimensions: interaction, continuity, and situation. Data were generated through in-depth interviews conducted online, and trustworthiness was ensured through member checking and expert review. The findings reveal that the teacher's initial experience was marked by significant difficulties in sustaining student attention and the inadequacy of conventional teaching approaches. In response, she adopted a multisensory and individualized approach centered on visualization, movement, repetition, and positive reinforcement. Over time, song-based activities, most notably the use of